2010
DOI: 10.3944/aott.2010.2133
|View full text |Cite
|
Sign up to set email alerts
|

Selective Kirschner wiring for displaced distal radial fractures in children

Abstract: Our data suggest that there should be other factors involved in the development of redisplacement and the need for remanipulation other than the degree of fracture displacement and the quality of initial reduction. Selective K-wire fixation in displaced fractures does not seem to decrease redisplacement and remanipulation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…Many studies have been performed to identify risk factors for redisplacement showing varying results. Several studies recommended additional K-wire fixation for not optimally reduced distal radius fractures, while others recommended additional K-wire fixation for all completely displaced fractures, even after an acceptable closed reduction [ 7 , 9 , 15 , 16 ]. More recently, the quality of cast moulding was evaluated as a potential risk factor for redisplacement, however, without univocal results [ 5 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed to identify risk factors for redisplacement showing varying results. Several studies recommended additional K-wire fixation for not optimally reduced distal radius fractures, while others recommended additional K-wire fixation for all completely displaced fractures, even after an acceptable closed reduction [ 7 , 9 , 15 , 16 ]. More recently, the quality of cast moulding was evaluated as a potential risk factor for redisplacement, however, without univocal results [ 5 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 , 23 ] Therefore, a number of surgeons recommend pinning to augment the reduction to prevent re-displacement. [ 24 , 25 ] In all 6 papers, our review found significantly higher re-displacement rates in the casting therapy group. [ 13 , 17 21 ] Overall, the mean re-displacement rate found in this systematic review was 40.0% in the casting group compared with 3.6% in the pinning group (Chi-square tests, P < .001).…”
Section: Discussionmentioning
confidence: 89%
“…Um eine sekundäre Dislokation sicher vermeiden zu können, wird von vielen Autoren eine primäre Reposition mit perkutaner K-Draht-Osteosynthese gefordert [11,12,18]. Obwohl diese die sekundäre Dislokation weitgehend verhindert, gibt es keine belastbaren Daten zu den Langzeitergebnissen, die in einem Cochrane-Review dringend gefordert werden [1,13].…”
Section: Grünholzfrakturen Und Komplette Frakturen Mit Angulationunclassified